Responding to the changing WASH needs in Mali - Oumar Samake; Aly Sow; C. Chiaka; Alassane Maiga; F. Haidara; M. Diarra; N. Traore (2013)
The political unrest that started in Mali on the 21st of March 2012 has had a significant impact on access to safe water and sanitation for an estimated 1.9 million people. Like most development or non-humanitarian organisations, WaterAid Mali was forced to stop their water and sanitation interventions in northern target communities due to insecurity. In the south, water, sanitation and hygiene needs changed quickly, as a result of the large number of people migrating from the north. WaterAid Mali has adapted to these changes through reallocating resources, implementing new activities and internal capacity building. This paper will discuss the experiences of WaterAid Mali as well as the lessons learnt.